Isoflurane does not protect from brain death-associatedaggravation of cold hepatic ischemia-reperfusion injury - Strowitzki, Moritz; Moussavian, Mohammed Reza; Keppler, Ulrich; Schilling, Martin K.; Menger, Michael D.; Heesen, Maximilian von (Annals of transplantation, 2015)
[b]Background[/b] - Previous studies have shown that brain death aggravates cold ischemia-reperfusion injury in liver transplantation. Isoflurane, a volatile anesthetic, has been indicated to reduce warm hepatic ischemia-reperfusion injury. Herein, we studied in Sprague-Dawley rats whether isoflurane is capable of ameliorating brain death-associated aggravation of cold hepatic ischemia-reperfusion injury. - [b]Material and Methods[/b] - Brain-dead animals were treated for 30 min with isoflurane (MAC 1.5%; n=8). Animals without isoflurane treatment served as controls (n=8). Another 13 animals without induction of brain death served as sham controls. After a 4-h period portal venous blood perfusion, hepatic microcirculation and bile flow were determined. Livers were recovered and stored for 24 h in 4°C cold HTK solution, followed by reperfusion with 37°C Krebs-Henseleit-buffer for 60 min. Liver enzymes in the effluent and bile flow were analyzed. Hepatocellular morphology was determined by histology and immunohistochemistry. - [b]Results[/b] - Brain death reduced portal venous blood perfusion and bile flow, induced heme oxygenase-1 (HO-1), and resulted in hepatocellular damage. Isoflurane treatment did not prevent the reduction of portal venous blood perfusion or bile flow or the induction of HO-1. Accordingly, isoflurane was not capable of reducing the hepatocellular injury. - [b]Conclusions[/b] - Isoflurane does not protect from brain death-associated aggravation of cold hepatic ischemia-reperfusion injury.